Intention to adopt halal concept in online food delivery meatball restaurants - Ikawati, Retty; Erwanto, Yuny; Purnomo, Boyke Rudy (Faculty of Business & Economics, Universitas Islam Indonesia, 2025)
Purpose – This study aimed to analyze the impact of engagement, personal norms, perceived organizational readiness, and behavioral controls on meatball partners' intentions to adopt halal concepts..Methodology – The Respondents are the meatball partner OFD in Yogyakarta and Solo Raya, gathering 195 respondents through purposive sampling. The number of samples determined follows Roscoe's principle. The information gathered was analyzed using Structural Equation Modeling (SEM) in conjunction with Partial Least Squares (PLS) techniques to determine the relationships between the different factors.Findings – The results indicated that religious commitment, halal awareness, personal characteristics, perceived behavioral control, subjective norms, and attitudes do not affect the intentions of meatball partners to apply the halal concept, contrary to TPB theory in influencing the intention to perform a behavior. On the contrary, the obligation of halal certificates and organizational readiness has a positive effect on the intentions of meatball partners to apply the halal concept..Implications – It is necessary to increase entrepreneurs' awareness of halal and their religious commitment. Halal obligation and organizational preparedness are two factors that significantly influence partners' intentions to implement the halal concept. Because it takes the combined efforts of all members, strengthening the organization becomes a source for producers.Originality – Its examination of the application of the halal concept to meatball partners incorporated in online applications. It contributes to the understanding of the impact of engagement, personal norms, perceived organizational readiness, and behavioral controls on meatball partners' intentions to adopt the halal concept.